Role of Digital Technology in Transforming Organizational Competencies Influencing Green Economy: Moderating Role of Product Knowledge Hiding - Bai, Haoran (Frontiers in Psychology, 2021)
Digital technology has gained momentum in the recent decade, with its relationships with digital entrepreneurship, digital economies, digital social interaction, green economies, etc. These have changed the perspective of business and hence digitalized the strategic policies through blockchains. The current study aims to identify such benefits that have changed the day-to-day life processes and procedures for carrying out different tasks due to the convenience of adopting digital technology. Those benefits have been classified as transparency, centralization and access to new markets for the organizations considering their consequences, especially when using digital technology. When processes are taking place online on the internet, there are fair chances of hiding knowledge about certain products or procedures to gain particular benefits. Hence, this study has considered the moderating role of product knowledge hiding while interacting online on the internet. This study is a quantitative post-positivist cross-sectional study that has followed a survey technique for data collection. The population used in this study is the managerial staff of the telecom sector in the mainland in China. The sample size used in this study is 358. The software used in this study is smart pls 3.3. The technique used in this study for data analysis is structural equation modeling with measurement modeling. The findings of this study show that digital technology has led to many benefits for organizations like centralization, access to the new markets, and transparency have been made possible remotely only because of the use of digital technology in business operations. However, the moderating role of product knowledge hiding has been found significant only for transparency. This research paper highlights the important benefits of the use of technological use in the corporate world. Also, it contributes to expanding the network of knowledge hiding, addressing the moderation of product knowledge hiding and extending the known consequents of digital technology influencing knowledge hidings.